L’adaptation scolaire des étudiants LGB issus de l’immigration au Québec : quels liens avec le processus de coming out? - Brais-Dussault, Elsa; Villatte, Aude (Canadian Journal of Higher Education, 2022)
Using the concept of intersectionality, this article seeks to determine: 1) whether LGB (lesbian, gay, bisexual) youth from immigrant backgrounds (i.e., "double minority" youth) report more academic difficulties compared to those from single (sexual or ethnocultural) or no minority backgrounds; and 2) whether having disclosed one's sexual orientation to the majority of one's network is associated with better academic adjustment among LGB youth from immigrant backgrounds. The sample consisted of 5,561 postsecondary students (ages 18-30) from Quebec institutions and was divided into four groups: no minority (73.1%), single sexual minority (8.7%), single ethnocultural minority (16.8%), and double minority (1.4%). These youth completed an electronic questionnaire (Winter 2017) assessing their academic adjustment from different perspectives: social adjustment, academic adjustment, attachment to the institution, and academic goals. Latent class analyses identified six student profiles of academic adjustment. Binary and multinomial logistic regression analyses controlling for the effect of gender, parental education, and level of financial insecurity then showed that (a) dual minority students were less likely to report an overall positive academic experience than non-minority or single minority students; and (b) having disclosed one's sexual orientation to the majority of one's network was associated with a higher likelihood of having an overall positive academic experience among LGB youth with immigrant background.